To What Do People Contribute? Ongoing Operations vs. Sustainable Supplies - Yuval Arbel; Ronen Bar-El; Mordechai E. Schwarz; Yossi Tobol (Institute of Labor Economics (IZA), 2019)
We study how the objective of the contributions affects the willingness to contribute to real-life public goods. We conducted three treatments of a fundraising experiment among religious Jewish students in which the contributions were assigned to finance sustainable supplies and the ongoing operations of their campus synagogue. In each treatment, we informed the subject of the different allocation of their contributions between funding sustainable supplies and ongoing operations. The results show that contributions increase significantly with the share of contributions assigned to the procurement of sustainable supplies. We use the results to derive practical implications for the design of fundraising for public goods.
Keywords: C73; C91; C92; H41; 330; experiment; Nash equilibrium; public goods; voluntary provision